A view from the clinic – Perspectives from Dutch patients and professionals on high myopia care. (17th January 2023) - Ravenstijn, Monica; du Bois, Gerlof; Jansen, Ritsert C.; Liu, Chang; Luyten, Gregorius P. M.; van Leeuwen, Redmer; Dickman, Mor M.; Reus, Nic J.; Yzer, Suzanne; Klaver, Caroline C. W.
Abstract: Purpose: To understand and compare perspectives of patients and professionals on current ophthalmologic care for high myopia, and to identify challenges and future opportunities. Methods: Self‐reported data were collected through two online questionnaires. Patient perspective was obtained from highly myopic members of a patient organisation based in the Netherlands using a 17‐item questionnaire consisting of open and multiple‐choice questions regarding personal experience with myopia care. The ophthalmologist perspective was obtained from practising Dutch ophthalmologists with a 12‐item questionnaire of multiple‐choice questions on work‐related demographics, myopia care in daily practice and need for improvement. The response rate for patients was 27% ( n  = 136/500) and for ophthalmologists, 24% ( n  = 169/716). Results: Patients were highly concerned about personal progressive loss of vision (69%) and feared their psychological well‐being (82%) in case this would happen. The quality of performance of care provided by ophthalmologists was rated as excellent or satisfactory by 64% of the patients. These ratings for multidisciplinary care and insurance reimbursement were as low as 28% and 18% respectively. The mean concern among ophthalmologists about the rise in high myopia was 6.9 (SEM 0.1) on a 10‐point scale. Sixty‐nine per cent of the ophthalmologists reported that asymptomatic myopic patients should not be examined regularly at outpatient clinics. Ophthalmologists urged the development of clinical guidelines (74%), but did report (95%) that they informed patients about risk factors and complications. This contrasted with the view of patients, of whom 42% were discontent with information provided by ophthalmologists. Conclusions: These questionnaires demonstrated that the current clinical care delivered to highly myopic patients is in need of improvement. The expected higher demand for myopia care in the near future requires preferred practice patterns, professionals specifically trained to manage myopic pathology, accurate and comprehensive information exchange and collaboration of in‐ and out‐of‐hospital professionals across the full eye care chain.